2020
DOI: 10.1038/s41598-020-59895-3
|View full text |Cite
|
Sign up to set email alerts
|

The Proteolytic Fraction From Vasconcellea cundinamarcensis Latex Displays Anti-Inflammatory Effect in A Mouse Model of Acute TNBS-Induced Colitis

Abstract: The proteolytic fraction (P1G10) from Vasconcellea cundinamarcensis, displays gastric protective and healing activities in different skin lesions in mice and human. In an excisional model, this fraction accelerates resolution of lesions and modulates inflammatory mediators. Based on these data, we assessed its anti-inflammatory activity in murine colitis model, induced by 2,4,6-trinitrobenzenesulfonic acid (TNBS) adopted by its physiopathological similarity with human colitis. Twenty four hours after colitis i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…7 A, B). The neutrophil infiltration was an important feature of colitis model [ 23 ]. Myeloperoxidase (MPO) in the model group was significantly increased, indicating the severe neutrophil infiltration in colon.…”
Section: Resultsmentioning
confidence: 99%
“…7 A, B). The neutrophil infiltration was an important feature of colitis model [ 23 ]. Myeloperoxidase (MPO) in the model group was significantly increased, indicating the severe neutrophil infiltration in colon.…”
Section: Resultsmentioning
confidence: 99%
“…Vasconcellea cundinamarcensis is native to tropical America[ 177 ]. The in vivo investigation revealed that the proteolytic fraction (P1G10) is composed of 14 proteolytic isoforms that protect and repair the stomach by raising mucus content, lowering gastrin levels to avoid hyperacidity, improving excisional wound healing, and boosting PGE2 production[ 178 ]. P1G10 was investigated as a natural antifungal and shown to be capable of inhibiting mycelium development and cell adhesion in B. cinerea by inducing membrane integrity and cell wall degradation[ 179 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, peptidases can degrade membrane proteins by altering their permeability and allowing the uncontrolled flow of substances through the cell [ 24 ]. Regarding the pharmacological properties that have been attributed to P1G10, a recent study that shows a protective effect on gastric ulcers and healing activities in different skin lesions in mice and humans stands out [ 59 ]. Therefore, in addition to the antifungal activity that P1G10 possesses, this fraction could add value to grape juice.…”
Section: Discussionmentioning
confidence: 99%